Dynamic Scoring of Tax Reforms in the EU - Mathias Dolls; Christian Wittneben (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
In this paper, we present a dynamic scoring analysis of tax reforms for EU countries, accounting for the feedback effects resulting from the adjustment in labour supply and economy-wide reaction to tax policy changes. We combine the microsimulation model EUROMOD incorporating an estimated labour supply model, with the new Keynesian DSGE model QUEST used by the European Commission. We illustrate the results obtained when scoring specific reforms in three EU Member States.
Keywords: 330